A new mode of inheritance!. (4th April 2011) - Koodiyedath, B; Bowen, J; Johnson, D; Sharrard, M
Abstract : Glycogen storage diseases (GSDs) are defects of glycogen metabolism or glycolysis. GSD type IX is the most frequent and is a heterogeneous condition caused by deficiency of phosphorylase kinase enzyme (PHK), the key enzyme in the breakdown of glycogen. Children present with fasting hypoglycaemia and occasionally hepatopathy and myopathy. The mode of inheritance is X linked or Autosomal recessive. PHK enzyme is a decahexameric holoenzyme composed of four of each of the subunits: α, β, γ, δ. (figure 1 ). There are liver and muscle isoforms containing different α, PHKA2 gene (X linked) and γ, PHKG2 (Autosomal)) subunits but the same β and δ (Calmodulin) subunits. The β subunit is coded by PHKB located on chromosome Chr 16q12-q13. Case history: 19 month old boy experienced recurrent symptomatic ketotic hypoglycaemia. Erythrocyte PHK was deficient 0.75 μmol/ml/gmHb (Normal range 10–90) with normal glycogen content and normal leukocyte glycogen phosphorylase and debrancher. Sequencing of PHKB showed heterozygosity for a novel missense mutation in exon 6 of PHKB (p.[=]+[Tyr167Cys]) and no mutation in PHKA2 (α subunit) or PHKG2 (γ subunit). Both PHKB allelles generated stable mRNA transcripts. The mother and the half-brother (by a different father) also experienced symptomatic hypoglycemia and had deficient PHK activity (Mother: 3.8 μmol/ml/gmHb and Half- brother: undetectable). Both were heterozygous for the (p.[=]+[Tyr167Cys]) mutation in PHKB. Usually PHKB gene mutations are recessive and 50% production of the β subunit is sufficient for normal enzyme function. In this case the β subunit is produced in altered form which disrupts enzyme activity. Each enzyme complex contains four β subunits. If any one of these four is mutated, the result is a defective enzyme complex with no activity and a total PHK activity 1/16 of normal. This mutation is thus causing an autosomal dominant negative inheritance effect, which has not previously explained in Glycogen storage disease. The recurrence risk in the child of an affected individual is 50%. A detailed family history and mutation analysis are important in determining the precise diagnosis and inheritance pattern and can be used for genetic counselling.